2D Game “Omar’s Adventure” design using the Finite State Machine Method - Rashad Fathin Kurniawan; Fresy Nugroho; Puspa Miladin Nuraida Safitri Abdul Basid; Firma Sahrul Bahtiar; Raihan Nafal Zuhdi Simamora; Geovanni Azam Janitra; Juniardi Nur Fadilah (Universitas Medan Area, 2022)
A video game is a game that has rules in it that must be obeyed when the game takes place so that the video game ends either in a win or a loss, played with a device / console. Video games themselves consist of various kinds, one of which is 2D video games. A 2D game is a game that only has 2 spaces or 2 axes, namely the X and Y axes. This research was conducted with the aim of incorporating Islamic elements into a video game so that players can recognize and learn Islamic elements through more interesting media. The result of the research is a 2D game called